Predictors of long-term stability of maxillary dental arch dimensions in patients treated with a transpalatal arch followed by fixed appliances - Raucci, Gaetana (Prog Orthod, 2015)
BACKGROUND: The aim of this retrospective study was to identify which dental and/or cephalometric variables were predictors of long-term maxillary dental arch stability in patients treated with a transpalatal arch (TPA) during the mixed dentition phase followed by full fixed appliances in the permanent dentition. METHODS: Thirty-six patients, treated with TPA followed up by full fixed appliances, were divided into stable and relapse groups based on the long-term presence or not of relapse. Intercuspid, interpremolar and intermolar widths, arch length and perimeter, crowding, and upper incisor proclination were evaluated before treatment (T(0)), post-TPA treatment (T(1)), post-fixed appliance treatment (T(2)), and a minimum of 3 years after full fixed appliances’ removal (T(3)). A binary logistic regression was performed thereafter to evaluate the impact of the dental arch and cephalometric measurements at T(1) and the changes between T(0) and T(1) as predictive variables for relapse at T(3). RESULTS: The proposed model explained 42.7 % of the variance in treatment stability and correctly classified 72.2 % of the sample. Of the seven predictive variables, only upper anterior crowding (p = 0.029) was statistically significant. For every millimeter of decreased crowding at T(1) (after TPA treatment/before starting the fixed orthodontic treatment), there was an increase of 3.57 times in the odds of having stability. CONCLUSIONS: The best predictor of relapse was maxillary crowding before treatment. The odds of relapse increase by 3.6 times for every millimeter of crowding at baseline.